Perlindungan Hukum Terhadap Nasabah Prima Bank dalam Resiko Layanan Pick Up Service - Lorensa, Shella Amilia; Badriyah , Siti Malikhatun (LPPM Universitas Ekasakti Padang, 2023)
Banks as financial service institutions have special customers, namely prime customers. Prime customers have a special service, namely pick up service. Implementing a pick up service can pose various risks. The risk that occurs in the pick-up service causes losses experienced by prime customers. This writing aims to find out, study and analyze legal protection for prime bank customers in the risk of pick up service. This legal research uses normative juridical methods. The results of the discussion show that legal protection can be provided to prime customers in the risk of pick-up service, namely preventively and repressively. Preventive legal protection can be provided through legislation to prevent risks occurring in pick-up services. Meanwhile, repressive legal protection can be provided by imposing administrative sanctions in the form of fines and providing additional sanctions to the Bank if it discharges its responsibility for losses experienced by customers from services provided by the Bank.